SOME BASIC ASSUMPTIONS UNDER LYING SOCIAL ACCOUNTING. - Farman, Wilson L. (The Accounting Review, 1951)
Abstract The article discusses some of the basic assumptions underlying social accounting. The basic idea is simply that the social accounting data must be scrutinized thoroughly before the results of social accounting can be interpreted properly. If this is not done and social accounting data are taken at their face value, they are apt to be misused and misinterpreted because of incomplete awareness of their underlying assumptions. In social accounting, as in private accounting, one must make some initial decisions. Social Accounting, that is, a system of accounts for a community, has three main functions: to provide a running, historical record of the community's economic operations; to measure the efficiency with which the community's economy operates; to provide a periodic inventory. The basic assumption concerning goals of economic activity can thus range from recognizing none except sheer increase of capacity as measured by population and capital to recognizing several so that the flow of several categories of products is taken at their gross value.